Numerical Simulation of Air Diffusion in Water with Venturi Type Injector for Applications in Freshwater Aquaculture Biofloc Systems - Yulianto, Eri
ndonesia has a large potential of fishery resources, both in capture fisheries and aquaculture resources. In fish farming activities, one of the important issues that must be considered is the concentration of ammonia from fish feed and feces. The biofloc system is one of the most widely applied cultivation systems because it can deal with problems in aquaculture efficiently. Oxygen supply is important in the fish farming, especially for biofloc systems. Oxygen needs can be fulfilled with venturi type injector. The working principle of venturi type injector is to create a different pressure between pressures of the outside air with pressures of the fluid in the pipe until it reach the vacuum point of pressure therefore the air will be absorbed into the venturi. Because the flow at the outlet is turbulent, air bubbles will form. The smaller the bubble will have a rising velocity and will remain in the water longer which will generate the increase of oxygen levels in the water or DO (dissolved oxygen). In this undergraduate assignment is conducted a simulation of a venturi Air Injector type with variations in water debit parameters of 13 lpm, 15 lpm, and 17 lpm to meet the 288lpm oxygen demand that will be fulfilled by eight venturi OG types. One OG is intended to produce 40 lpm air. Numerical simulations were assessed with Ansys Fluent 19.2 software. Results of the air flow that obtained through numerical simulations are rising velocity of 224 mm/s for water debit of 13 lpm, rising velocity of 119 mm/s for water debit of 15 lpm, and rising velocity of 56,9 for water debit of 17 lpm. While, the power for one venturi is 11,8 watts for 13 lpm water debit, 19,6 watts for 15 lpm water debit, and 28 watts for 17 lpm water debit.